'Mat' this and 'Mat' that - Abd Razak, Dzulkifli (2006)
WE call the illegal motorcycle racers Mat Rempit. Such labelling of people is not new with Malaysians. Forty years ago, Minah Karan was a popular monicker attributed to women workers in the electronic industry that was in its infancy in the country at the time. The somewhat derogatory label referred to the tens of thousands of young and naive girls from the kampungs who were rooted out to serve as "cheap labour" in an industry viewed sceptically by many. For the majority of the girls, this was the first time they were leaving home. Economically, times were not good for many families back then and this was a chance to earn extra income. They dreaded leaving home to face an uncertain future. The availability of Minah Karan was one of the pull factors that convinced the foreign players to invest in a the new industry. They were desperate to keep the cost of production down.